2009
DOI: 10.1583/08-2656.1
|View full text |Cite
|
Sign up to set email alerts
|

Atherectomy for Infrainguinal Peripheral Artery Disease

Abstract: Compared to conventional percutaneous transluminal angioplasty (PTA) and stent implantation for arterial occlusive diseases, atherectomy offers the theoretical advantages of eliminating stretch injury on arterial walls and reducing the, rate of restenosis. Historically, however, neither rotational nor directional atherectomy, whether used alone or with adjunctive PTA, has shown any significant long-term benefit over PTA alone in the coronary or peripheral arteries. However, the SilverHawk Plaque Excision Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 61 publications
0
28
0
1
Order By: Relevance
“…For larger vessels such as the CFA, there is a question about primary patency after atherectomy, and the ability of the device to be sized sufficiently to fully treat the large vessels. 10 Catheter-based therapy of the CFA has only been described in a few studies to date. In 27 patients with angioplasty and stent implantation in 33 limbs involving the CFA, technical success was achieved in 100% of the cases with a cumulative primary patency of 83% at 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…For larger vessels such as the CFA, there is a question about primary patency after atherectomy, and the ability of the device to be sized sufficiently to fully treat the large vessels. 10 Catheter-based therapy of the CFA has only been described in a few studies to date. In 27 patients with angioplasty and stent implantation in 33 limbs involving the CFA, technical success was achieved in 100% of the cases with a cumulative primary patency of 83% at 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent randomized trial has demonstrated significantly higher primary patency rates of stenting vs. PTA of femoropopliteal artery lesions TASC A and B at 1-year follow up [7]. However, several alternative endovascular options are available, including subintimal angioplasty, cryoplasty, cutting balloon angioplasty, primary as well as adjunctive deployment of self expanding bare nitinol or covered stents, and ablative modalities such as excimer laser and directional plaque excision [3]. The long term results of these techniques are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, external stent compression in this district may cause restenosis and also stent erosion, and finally fracture when it occurs repeatedly [4]. In contrast, atherectomy offers the theoretical advantages of eliminating stretch injury on arterial walls and reducing the rate of restenosis [3]. In addiction, it removes the obstructing atherosclerotic or intimal hyperplastic lesions without the disadvantage of a foreign body such as a stent in the artery [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAD can be treated with minimally invasive procedures such as percutaneous transluminal angioplasty, stenting, or cutting of the plaque (i.e., atherectomy) [29][30][31]. In more severe cases, surgery may be necessary to graft a transplanted artery to bypass the blockage.…”
Section: Symptoms and Treatment Strategies For Peripheral Artery Diseasementioning
confidence: 99%